List of bats register at high altitudes in Río Abiseo National Park - Romo, Mónica (2023)
We present a list of bats collected above 2000 meters in Río Abiseo National Park. Sixteen bat species belonging to the Phyllostomidae and Vespertilionidae families were collected during four expeditions between 1987 and 1990. Twelve species were found within expected altitudinal ranges, but four exceeded their previously reported maximum altitudinal ranges. A comparison with other bat lists from other localities at similar altitudes is presented.